"Half-sandwich" YbIII single-ion magnets with metallacrowns1. Issue 51 (28th June 2015) - Li, Quan-Wen; Liu, Jun-Liang; Jia, Jian-Hua; Chen, Yan-Cong; Liu, Jiang; Wang, Long-Fei; Tong, Ming-Liang
<x xml:space="preserve">Abstract</x> Two "half-sandwich" YbIII-SIMs are presented bearing metallacrowns. The central ytterbium ion is coordinated by YbO8 geometry in D4d symmetry. The analysis of static, dynamic magnetism and emission spectrum offers an insight into the magneto-optical correlation.